E-politics from the citizens’ perspective. The role of social networking tools in influencing citizens - Kapsa, Izabela (Przegląd Politologiczny, 2018)
The progress of civilization, supported by the development of new technologies, has led to a series of social, economic and political changes. The information society, in its expectations and through access to knowledge, has significantly affected a change in the model of democracy, causing a kind of return to the original forms of communication in citizen-government relations. This has been accompanied by a shift of social and civic activism from the real to the virtual world. In literature, the use of information and communication technologies in the democratic system is named electronic democracy. One of its forms is e-politics, which is implemented at several levels: institutional, system and civil. A good example of the last type are the new social movements that in recent years have had a significant impact on politics. The basic research problem in this paper concerns e-politics from the citizens’ perspective, through the activities of the new social movements, especially of a political nature. The main research goal is therefore to present the role of social networking tools in influencing citizens and their subsequent activities that have triggered changes in the political system. The methods used in the paper are case study and comparative analysis.